Analisis Penggunaan EPA (Evaluasi Penyuluhan Agama) Pada Kementrian Agama Provinsi Aceh Kabupaten Bener Meriah - Khasnita Sari; Laylan Syafina (Jurnal Kendali Akuntansi, 2024)
This study aims to determine the role of Islamic Extension Workers in empowering the economy through the basic food business carried out by the Ministry of Aceh Province, Bener Meriah Regency. The approach used in this study is descriptive qualitative, that is, after the data has been collected, a qualitative analysis is carried out and describes one data with other data in such a way as to obtain a complete general picture of the problem under study. Then the data collection method uses observation, interviews, and documentation. In determining research subjects, the authors use purposive sampling technique with informants one taklim board of directors, one person in charge of the basic food business and three worshipers.The results of this study are: Islamic religious instructors carry out informative/educational and consultative roles as well as the implementation of expected roles and actual roles and Result of the economic empowerment is the formation of financial independence of the taklim assembly and the creation of the congregation's ability to meet basic needs.